2009
DOI: 10.1177/1363461509342948
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Clinicians’ Use of the Cultural Formulation Model in Assessing Posttraumatic Stress Disorder

Abstract: The Cultural Formulation of Diagnosis (CFD) Model of the Diagnostic and Statistical Manual (DSM) provides a potential framework for improving the diagnostic assessment of Posttraumatic Stress Disorder (PTSD) in culturally diverse patients. We analyzed data from the Patient-Provider Encounter Study, a multisite study that examines the process of diagnosis and clinical decisionmaking during an initial clinical intake session, in order to examine use of CFD for PTSD diagnosis. We find that the use of the CFD in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…72,74 Many excluded papers presented accounts of the cultural formulation, and its use as part of the formal psychiatric assessment process, yet none evaluated the cultural formulation, or offered a sufficiently critical evaluative statement. 87,107 In the new edition of its diagnostic manual Diagnostic and Statistical Manual of Mental Illness-Fifth Edition (DSM-V), 108 the American Psychiatric Association has included a section on the 'Cultural Interview' that promotes the assessment of cultural factors (at least this area is no longer in an appendix, as it was in previous editions of the manual) and sets out guidelines. However, this approach needs evaluation and some have expressed a concern that the approach will not be well known or widely adopted by practitioners.…”
Section: Other Study Designsmentioning
confidence: 99%
“…72,74 Many excluded papers presented accounts of the cultural formulation, and its use as part of the formal psychiatric assessment process, yet none evaluated the cultural formulation, or offered a sufficiently critical evaluative statement. 87,107 In the new edition of its diagnostic manual Diagnostic and Statistical Manual of Mental Illness-Fifth Edition (DSM-V), 108 the American Psychiatric Association has included a section on the 'Cultural Interview' that promotes the assessment of cultural factors (at least this area is no longer in an appendix, as it was in previous editions of the manual) and sets out guidelines. However, this approach needs evaluation and some have expressed a concern that the approach will not be well known or widely adopted by practitioners.…”
Section: Other Study Designsmentioning
confidence: 99%
“…Cross-cultural research has shown evidently that culture shapes belief systems and thus influences the perception of traumatic events and their meaning, attribution and coping behaviours [76]. Given the importance of cultural context of traumatic experience, the use of DSM-IV Cultural Formulation has been in recent use for diagnostic formulation of patients of PTSD [36].…”
Section: Resultsmentioning
confidence: 99%
“… 53 , 55 Many excluded papers presented accounts of the cultural formulation (as described in the DSM-IV, 66 and now in modified form in DSM-5 67 ), and its use as part of the formal psychiatric assessment process, yet none evaluated the cultural formulation, or offered a sufficiently critical evaluative component for these studies to enter the review. 68 , 69 …”
Section: Discussionmentioning
confidence: 99%